Investigation of price formation in different commodities in the seaborne trade : LNG - Poh, Ping Shuang (2016)
This study mainly focuses on the investigation of the price formation of Liquefied Natural Gas (LNG) through analyzing the factors that contributes to price volatility of the commodity. The main driver behind this paper is due to the increasing global demand of LNG due to expansion in global population, increasing environmental concerns and supply security issues of other energy sources. The paper will discuss individually how economical and exogenous factors such as political, technological, environmental and social factors affect the commodity pricing. The analysis will be broken down over three different time periods 2005 – 2007, 2008 – 2010 and 2011 – 2015. At the same time analysis will be restricted to three main regions which is the United States of America (USA), Europe and Asia. When the paper first investigated price formation in the three regions, prices in Europe and Asia were still largely correlated to global oil prices. Europe started switching to a hybrid pricing system in 2009 and Asia’s prices are still oil-linked despite efforts to shift away. In the U.S LNG prices use Henry Hub spot price as a benchmark instead of oil-linked ones. Government policies and global regulations play a significant part in determining the demand and supply of energy sources in countries. In addition, the demand of energy varies with the weather as it affects the demand for heating and cooling systems. Technology advancement has brought down the cost of constructing LNG infrastructures and supplying renewables. The significance of factors affecting LNG prices varied across the three time-period and due to changing market conditions, there are new factors contributing to the volatility in LNG prices. The turning point for LNG market will not happen before 2020 as demand is likely to balance out with supply levels by 2021. This will result in a slow and stable increase in LNG prices. Future papers can look into methods which can reduce market volatility through resolving issues related to long-term oil-linked contracts.